Pelatihan Pemanfataan Kelas Daring New Edmodo dalam Pembelajaran Tematik di Sekolah Dasar Muhammadiyah Singkut - Andi Suhandi; Issaura Sherly Pamela (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
During the pandemic, learning is done from home. Learning from home is constrained by activity, participation, and monitoring of student activities during learning. This is the basis for teachers to innovate in learning. The use of applications or learning platforms can help teachers in delivering material and increasing student activity. One of the learning platforms that can be used is Edmodo. Teachers at SD Muhammadyah Singkut are not familiar with Edmodo. Training is needed so that teachers can use Edmodo smoothly. The main purpose of the PPM activity at the Muhammadyah Singkut Elementary School is to provide the latest knowledge regarding the use of new Edmodo as an online class during the pandemic. Specifically, the training objectives are 1. To provide information on the use of new Edmodo features to create active learning through Edmodo online classes. 2. Provide learning design knowledge through new edmodo. 3 Provide knowledge on applying online learning through new edmodo. The training is accompanied by mentoring and evaluation activities. The target is the Muhammadyah Singkut Elementary School teachers will transfer the knowledge gained during the training to teachers in the Teacher Working Group (KKG). The method used in this training is carried out in six stages, namely expository, question and answer, analyzing learning videos, practice of designing online-based active learning, presentations by simulating learning and reflection. The activity steps are carried out systematically. The training plan begins with the activity of providing information about active learning online. What strategies can be applied in learning and what applications can be used in learning. The second step involves questions and answers conducted in small groups. The third step is to analyze the learning video, this activity provides an opportunity for the teacher to see the active learning carried out by the model. When analyzing the teacher was asked to note the good and bad things in learning. The fourth step is to design active online-based learning in small groups and provide assistance. The fifth step is to present the draft prepared. Other participants are directed to be students and observers. This method ends with reflection, where the reflection activity is an activity to see the abilities and skills of the teachers after the training is complete. This activity is also an evaluation of the implementation of PPM. The training will produce an online active learning planning product that is prepared by the teacher during PPM activities. This community service has resulted in an increased understanding of teachers in integrating online learning through Edmodo. The online learning design through the Edmodo application was developed by the teacher during the training. New understanding of teachers in learning through Edmodo. The results of the questionnaire showed 87% of teachers' understanding to be applied in learning.